Productivity, prices and profitability: a case study of APSRTC - Singh, Sanjay Kumar (2001)
In this paper, the link between productivity, prices and profitability is examined for the Andhra Pradesh State Road Transport Corporation (APSRTC), using its annual data afrom 1979-80 to 1999-2000. We find that, by and large, productivity gains achieved by APSRTC are being passed through to customers. However, the data reveal a significant change in the pattern during the 1990s, particularly from 1995-96 onwards. During this period, on average the productivity of APSRTC declined, whereas its input factor prices compared with output prices increased significantly. This has resulted in a deterioration of its financial condition. - Reproduced
Keywords: Transport